Speech recognition for Malay Language to command & control computer program / Mohd Junaidi Jusoh - Jusoh, Mohd Junaidi (Faculty of Computer and Mathematical Sciences, 2007)
Speech recognition systems has been well-used by many people around the world. However, most of the systems are in English language and not suitable or unable to recognize speech in Malay language. This is due to the recognition engine is built specifically to recognize speech in that particular language only. The objective of the research is to develop a speech recognition system that able to recognize spoken word in Malay language and to perform typing simply by speaking. The analysis, design and development of the automation system are done in MATLAB, in which an isolated word speaker dependent speech recognizer is developed.